Genetic Relationships of Cassava Genotypes That are Susceptible or Tolerant to Cassava Brown Streak Disease in Uganda - Abaca, Alex; Kawuki, Robert; Tukamuhabwa, Phenihas; Baguma, Yona; Pariyo, Anthony; Alicai, Titus; Omongo, C. Christopher; Abidrabo, Phillips; Katono, Kasifa; Bua, Anton (Journal of Agricultural Science, 2013)
A total of 99 cassava genotypes whose field reaction to cassava brown streak disease (CBSD) was known, were assayed with 30 simple sequence repeat (SSR) markers to establish their genetic parallels. Two categories of CBSD reaction were considered: CBSD-susceptible genotypes (characterized by > 60% root and foliar CBSD incidence), and CBSD-tolerant genotypes (characterized by < 15% root and foliar CBSD incidence). DNA was extracted from leaf samples using the miniprep method and genotyped using ABI 3730 DNA sequencer. The test genotypes at 0.02 similarity coefficient, CBSD-tolerant and CBSD-susceptible genotypes clustered into 5 main sub-clusters. When data were subjected to principle component analysis (PCA) irrespective of the CBSD reaction grade, the first three principal components accounted for 68% of the total genetic variation. Despite having different number of individuals, the observed heterozygosity (Ho) for CBSD-susceptible (Ho = 0.58) and CBSD-tolerant (Ho = 0.66) were comparable and provide scope for long-term CBSD breeding and/or gene tapping.
Keywords: Cassava brown streak virus; Cluster analysis; Foliar symptoms; Simple sequence repeat marker